Pemenuhan Gizi Ibu Hamil KEK melalui Program Pendampingan Ibu Hamil di Kelurahan Graha Indah Balikpapan - Rahmawati, Eli; Hariyani, Faridah; Noviasari, Damai (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
Nutritional problem due to prolonged lack of food intake is a Chronic Energy Deficiency (CED). There is a risk of impairing fetal growth and development which results in stunting, prematurity, birth defects, LBW, and fetal/baby death. Efforts to improve the nutritional status of pregnant women with CED include nutrition education through assistance by cadres/ health workers. The purpose of this community service is to assist in fulfilling the nutrition of pregnant women with SEZ through home visits. Assistance methods include nutrition education, PMT, giving blood supplement tablets and multivitamins, and ANC checks. Assistance was carried out 2 times: first pretest nutrition education, PMT, blood tablets, and multivitamins, second 2 weeks from the first visit to monitor pregnancy conditions, and post-test. The number of participants was 20 people. The results of the activity increased knowledge from the average pre-test score of 7 to 11, on the attitude of the average score of 12 to 16, and behavior from the average score of 9 to 13. The results of statistical tests using the Wilcoxon Test obtained a value of p = 0.000. This explains that there is a significant increase in knowledge, attitude, and behavior before and after the assistance of pregnant women. It is hoped that assistance in fulfilling the nutrition of pregnant women with CED can improve the fulfillment of nutrition for pregnant women with CED, reduce the risks that occur to mothers and babies, and can be used as one of the programs in preventing stunting.